Phosphate fertilization to improve yield and chemical composition of banana ‘BRS SCS Belluna’ fruit - Cândido, Hebert Teixeira [UNESP]; Leonel, Magali [UNESP]; Leonel, Sarita [UNESP]; Rodrigues de Jesus, Paulo Ricardo [UNESP]; Ouros, Lucas Felipe dos [UNESP]; Molha, Nicholas Zanette [UNESP]; Domiciano, Vinícius Martins [UNESP] (Taylor & Francis, 2024)
Phosphate fertilization improves banana yields, but due to the physiological effects of phosphorus on plants, it can also be used to improve the physical and chemical characteristics of the fruits, which can contribute to increasing the processing of green bananas and reducing losses in the production chain. Herein, the productivity of bunches and fruit, the biometric analysis of the fruit, dry matter content, and the chemical composition of immature fruit were evaluated when the cultivar BRS SCS Belluna (AAA) was grown under different levels of phosphate fertilization for two harvest cycles. The results showed that phosphate fertilizer levels interfered with bunch yield and fruit mass in both cycles, leading to yield gains of 44.3% (1st cycle) and 84.0% (2nd cycle) in bunches and 51.8% (1st cycle) and 81.9% (2nd cycle) in fruits. Fertilization promoted gains of up to 33.5% in fruit mass and enhanced the resistant starch content in the pulp, leading to an increase of 15.1%. The phosphorus, potassium, and calcium contents in green fruits increased with fertilizer levels in the first cycle, improving nutritional quality. These results have useful applications because they indicate that adequate management of phosphate fertilization can increase the potential of the cultivar for industrial processing of green fruits and the nutritional quality of the derived products.
Keywords: Green fruits; minerals; Musa (spp.); starch; thermophosphate